Design and implementation of a micro-power CMOS voltage reference circuit based on thermal compensation of Vgs. Issue 1 (January 2015) - Chouhan, Shailesh Singh; Halonen, Kari
Abstract In this work a simple all MOS voltage reference circuit has been proposed. To obtain reference output voltage, the thermal compensation has been generated by using a series composite NMOSTs. The voltage reference circuit has been fabricated in a standard 0.18 μm CMOS technology. The proposed circuit is capable of working for the supply voltage ranging from 1.25 V to 2 V. The maximum power dissipation of the proposed circuit is 0.48 μW at the supply voltage of 2 V. The measurement has been performed over a set of 10 samples. It resulted in the mean temperature coefficient (TC) of 19.302 ppm/°C for the temperature range of −40 °C to 85 °C. The measured mean line sensitivity is 2.217 mV/V for the supply voltage ranging from 1.25 V to 2 V at the room temperature. The measured mean power supply rejection ratio at 10 Hz and 1 MHz is −55.31 dB and −16.67 dB respectively for the supply voltage of 1.8 V. Moreover, the measured mean noise density without any filtering capacitor at 100 Hz and 100 kHz are <alternatives><inline-graphic xlink:href="ark:/27927/pgh30rpc3sz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />12.39μV/Hz</alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pgh30rpcmp2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.39μV/Hz</alternatives> respectively. Due to its simple circuit implementation, the active area of the circuit is 0.0077 mm2.